How Journalists Display the Meaning: Do Association Meanings Exist in the Articles? - Ega Sauly Sitio; Risma Sari; Suci Chairunnisa; Kristina Br Gultom (Journal of English Language Teaching and Literature, 2020)
This study aimed at delivering a brief explanation and discusses the types of the meaning of association based on Geoffrey Leech's theory (1974) in media studies. This study underlined some interesting finding related meanings include connotation meaning, social meaning, affective meaning, reflective meaning, and collocative meaning. This study uses a qualitative descriptive approach to describe how journalists display the meaning of association in the articles in the analysis section of the website and analyze data also in the form of words, phrases, clauses, and sentences. Before analyzing, the data are categorized into five categories based on the region of origin of the article, by using table. After all the data in the table are analyzed, the researcher makes a conclusion. The results of this study indicate that there are five types of associative meanings.